4/26 which simplified to 2/13
so 2/13 is the answer
Step-by-step explanation:
2-×^2
t(×)=3×
(s o t )(x)=st(×)=s(t(x))=2-(3×)^2=2-9x^2
(s o t)(-7) =2-9(-7)^2=2-9(49)= 2-441= -439
Answer:
A. 2⅓ and D.1
Step-by-step explanation:
We are required to select the values of x that makes the inequality x>½ true.
A. 2⅓
B. 0
C.-1½
D. 1
E.-¾
Options C and E are negative numbers and are therefore less than the positive number ½.
Option B(i.e. 0) is also less than ½ or 0.5 and therefore do not satisfy the inequality given.
Options A and D are greater than ½ and therefore satisfies the inequality given.